Ramifications of change management initiative: case study of First National Bank - Nthutang, Oagile Abednigo (My University, 2016)
The purpose of the study is to interrogate and assess change reception by Hogan Technology Quality Assurance (HTQA) employees and determine the extent of and reasons for the HTQA employee exodus that resulted from a change initiative. HTQA is a division of First National Bank (FNB) also known as FNB (HTQA). The organisation went through a major transition during 2010 subsequently resulting in approximately 20% of talented employees voluntarily leaving the organisation. It is possible that during change dysfunctional behaviour can come to the fore, and if not managed properly can yield negative results on the outcome of change. A literature review on change management models, management impact during change implementation, resistance to change as well as human dimensions during change was carried out to get a deeper understanding of the phenomenon under study. A qualitative approach was viewed as appropriate and adopted in order to collect rich descriptive data and realise a more comprehensive meaning and reason of the phenomenon being studied (Maree, 2007). Structured face-to-face interviews were carried out to gather information from participants in the vicinity; for other participants emails were used to collect data. Study implications as to the role of management were drawn based on the data gathered and thematic analysis in conjunction with literature review stipulations. The major themes that emerged, as to why employees voluntary left the organisation during a change intervention were identified as lack of information dissemination (lack of communication); scepticism; fear of the unknown and lack of employees' involvement during change execution. This indicates a lack of proper change management by management and the importance of employee involvement, focusing on interpersonal communication during change. Change is not just a happening, but an involved and evolving process.
MBA North-West University, Mafikeng Campus, 2016
Keywords: Change management; Employee involvement; Resistance to change; Employee turnover; Ramifications of change implementation